Maranta sophiana (Marantaceae), a new species from the Brazilian Amazon - Yoshida-Arns, Karla Norye; Fraga, Fernanda Ribeiro De Mello; Freire, Talvanis Lorenzetti; Braga, João Marcelo Alvarenga (Phytotaxa, 2019)
A new species of Maranta (Marantaceae) from the Brazilian Amazon is described and illustrated. This species belongs to Maranta subg. Maranta and has close affinities with M. linearis, from which it differs in its caulescent habit, absent petiole, pulvinus with deciduous tufts of erect trichomes on the adaxial side, very long inflorescence with many florescences, and longitudinally ridged ovary and capsule.